Interplay between Confinement, Twist Elasticity, and Intrinsic Chirality in Micellar Lyotropic Nematic Liquid Crystals - Dietrich, Clarissa F (Langmuir : the ACS journal of surfaces and colloids, 2021)
Recent studies have shown that lyotropic nematic liquid crystals (LLCs) are exceptional in their viscoelastic behavior. In particular, LLCs display a remarkable softness to twist deformations, which may lead to chiral director configurations under achiral confinement despite the absence of intrinsic chirality. The twisted escaped radial (TER) and the twisted polar (TP) are the two representative reflection symmetry breaking director configurations in the case of cylindrical confinement with homeotropic anchoring. We demonstrate how such reflection symmetry breaking of micellar LLCs under cylindrical confinement is affected by intrinsic chirality, introduced by the addition of a chiral dopant. Similarities and differences between the effects of intrinsic chirality on the defect-free TER configuration, and on the TP configuration incorporating two half-unit twist disclination lines, are discussed. In the TP case, topological constraints facilitate stable heterochiral systems even in the presence of a small amount of chiral dopant, with unusual regions of rapidly reversing handedness between homochiral domains. At moderate dopant concentrations, the TP structure becomes homochiral. At high dopant concentrations, for which the induced cholesteric pitch is much smaller than the diameter of the capillary, the cholesteric fingerprint structure develops